2015
DOI: 10.4321/s0211-57352015000100004
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias de género en el trastorno delirante

Abstract: RESUMEN: El objetivo de nuestro estudio fue explorar las diferencias de género en trastorno delirante (TD) comparando aspectos sociodemográficos, factores de riesgo, correlatos clínicos y características del curso del trastorno. La muestra se compuso de 50 pacientes con primer ingreso psiquiátrico y con diagnóstico de TD (según SCID-I para criterios DSM-IV). Los casos fueron evaluados retrospectivamente mediante la revisión de historia clínicas mediante el cuestionario OPCRIT 4.0 y un inventario diseñado por l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Comorbid mood disorders are frequent in patients with DD [13]. Roman-Avezuela and collaborators (2015) reported than women were more likely than men to present with comorbid depressive symptoms [14]. However, this is not consistent with the results of Wustmann and colleagues who found no gender difference in depression in DD [12].…”
Section: Unspecified Typementioning
confidence: 94%
See 1 more Smart Citation
“…Comorbid mood disorders are frequent in patients with DD [13]. Roman-Avezuela and collaborators (2015) reported than women were more likely than men to present with comorbid depressive symptoms [14]. However, this is not consistent with the results of Wustmann and colleagues who found no gender difference in depression in DD [12].…”
Section: Unspecified Typementioning
confidence: 94%
“…The persecutory subtype is the most frequent, but this fact, too, depends on sample characteristics and the setting of the investigation [12][13][14]. With regard to gender differences in the content of the expressed delusions, several studies have reported erotomanic delusions to be more common in women than in men [14], whereas others have not found any statistically significant gender differences in the content of delusions. Table 1 shows DSM-5 criteria for DD and subtypes of DD according to the content of delusions.…”
Section: Gender Differences In Delusional Disordermentioning
confidence: 99%